Infective aortitis caused by Corynebacterium striatum in a patient with twice orthotopic heart transplantation - Wei Xiang; Ling-Yun Kong; Peng Zou; Dong-Yan Shen; Xiu-Juan Wang; Fang Liu (BMC Infectious Diseases)
Abstract Background Infective aortitis (IA) with vegetation formation is a rare but potentially life-threatening complication in patients with heart transplantation (HTx). IA caused by Corynebacterium striatum (C. striatum) has scarcely been reported. Herein, we present a case of IA caused by C. striatum in a young man eight months after his second orthotopic HTx. Case presentation We present a case of IA caused by C. striatum in a young man eight months after his second orthotopic HTx. The clinical course was complicated by recurrent fever, persistent bacteremia, anemia, and multiple peripheral arterial embolisms. While transthoracic echocardiography (TTE) revealed normal cardiac valves and endocardium, transesophageal echocardiography (TEE) confirmed an intraluminal mass in the anastomotic site of ascending aortic. The patient declined surgical intervention but responded well to medical therapy. He got resolution of infection following 6 weeks of vancomycin and remained well upon 34 months of follow-up without recurrent fever or new embolic events. Conclusions This case highlights the importance of evaluating the anastomotic site of ascending aortic in the context of bacteremia for HTx recipients, especially when routine TTE shows no valvular or endocardial involvement.